If you need access and order - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
CAB Thesaurus Printed Thesaurus. CABI. 1999. Alphabetical Listing. 925 pp. ISBN 0 85199 364 8 GBP 130 E 214.85 Classified Listing. 331 pp. ISBN 0 85199 365 6 GBP 50 E 82.60 Complete set (Alphabetical + Classified). ISBN 0 85199 366 4